Smart irrigation and soil component test - Bhowmik, Tushar; Ahmed, Nafiz; Hassan, Emonul; Mamun, Abdullah Al (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.